2018
DOI: 10.1002/cyto.a.23493
|View full text |Cite
|
Sign up to set email alerts
|

Automation of the in vitro micronucleus assay using the Imagestream® imaging flow cytometer

Abstract: The in vitro micronucleus (MN) assay is a well‐established test for evaluating genotoxicity and cytotoxicity. The use of manual microscopy to perform the assay can be laborious and often suffers from user subjectivity and interscorer variability. Automated methods including slide‐scanning microscopy and conventional flow cytometry have been developed to eliminate scorer bias and improve throughput. However, these methods possess several limitations such as lack of cytoplasmic visualization using slide‐scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 60 publications
2
49
0
Order By: Relevance
“…In general, these approaches require that cells are exposed to a test chemical and grown to provide sufficient time for chromosomal damage and/or cell cycle proliferation defects to manifest, which are required for micronucleus formation. Many of these approaches involve microscopy, flow cytometry, or image-based flow cytometry and include the use of DNA counterstains (Giemsa or fluorescent DNA dyes), fluorescence in situ hybridization (FISH) probes (chromosome enumeration probes), or kinetochore antibodies to identify micronuclei and/or their contents [48][49][50][51][52][53][54]. As an alternative, our scQuantIM approach does not depend on the efficient inhibition of cytokinesis by cytochalasin B, a compound that by itself has been shown to induce genome instability [34,55] and could conceivably synergize with test compounds or gene silencing to exacerbate micronucleus formation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these approaches require that cells are exposed to a test chemical and grown to provide sufficient time for chromosomal damage and/or cell cycle proliferation defects to manifest, which are required for micronucleus formation. Many of these approaches involve microscopy, flow cytometry, or image-based flow cytometry and include the use of DNA counterstains (Giemsa or fluorescent DNA dyes), fluorescence in situ hybridization (FISH) probes (chromosome enumeration probes), or kinetochore antibodies to identify micronuclei and/or their contents [48][49][50][51][52][53][54]. As an alternative, our scQuantIM approach does not depend on the efficient inhibition of cytokinesis by cytochalasin B, a compound that by itself has been shown to induce genome instability [34,55] and could conceivably synergize with test compounds or gene silencing to exacerbate micronucleus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CBMN assay has been adapted to an IFCbased method for use in genetic toxicology testing (19,20) and triage radiation biodosimetry (21)(22)(23)(24)(25). These methods demonstrated that cellular images of both the cytoplasm and fluorescence-labeled nuclei and MN could be captured at higher throughput than other methods used to perform the assay.…”
Section: Introductionmentioning
confidence: 99%
“…BNCs and MN were automatically identified in the Image Data Exploration and Analysis Software (IDEASt) by using mathematical algorithms to implement BNC/MN scoring criteria (2,26). The IFC-based version of the CBMN assay has been shown to automatically score more BNCs than can be scored using manual microscopy in a fraction of the time, which enhances the statistical robustness and speed of the assay (19). For radiation biodosimetry, dose-response calibration curves from whole blood samples exposed to 0-4 Gy of X rays were created to quantify the frequency of MN per BNC (24).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has also been applied to replace the use of manual microscopy for the in vitro micronucleus assay used to study geno-and cytotoxicity. The use of IFC allowed for more automation and informative visualizations (3). IFC has also been used to study the partitioning of molecules across the plane of cell division in a statistically robust manner (4,5,6).…”
Section: Introductionmentioning
confidence: 99%